POST-TRANSCRIPTIONAL REGULATION OF POLYMORPHIC PROTEASE-ACTIVATED RECEPTOR-2 (PAR-2) GENE DISPLAYING CORRELATION WITH SKIN PIGMENTATION IN CATTLE - A. W. Nizamani; O. Fumière; L. Forestier; S. Presciuttini; H. Leveziel; 1 Z. A. Nizamani; A. Oulmouden (Journal of Animal and Plant Sciences, 2014)
Protease-activated receptor-2 (PAR-2) is a trypsin-activated member of the PAR receptor family. Following cleavage, the newly created N-terminus acts as a tethered receptor-activating ligand.PAR-2 is expressed in keratinocytes and enhances the phagocytosis rate of keratinocytes, which leads to increased melanosome transfer and skin pigmentation. Here, we investigated to see whether the bovine bPAR-2 plays a role in pigmentation of cattle skins resulting in shades ranging from dark-black to white. We have identifiedtwo bPAR-2natural variants located in the tethered ligand for the first time. Surprisingly, none of these seems to affect the receptor activity in relation to skin pigmentation as suggested by tethered ligand structure-activity relationships studies. Furthermore, we also showed for the first timethatbPAR-2is regulated at a post-transcriptional level in pigmentation-skin dependent manner. Modulation of PAR-2 activity enhances or decreases melanosome transfer from melanocytes to keratinocytes which results in a variation in skin pigmentation. In this study, we found that bPAR-2 was subjected to post-transcriptional regulation in pigmentation-skin dependent manner and that two variants affecting its tethered ligand did not affect skin pigmentation. Understanding the regulation of PAR-2 expression and the activity of its tethered ligand is important, because PAR-2 is involved in a key step of skin pigmentation and plays a role in lightening or darkening of the skin.
Keywords: Cattle; PAR-2; skin pigmentation; post-transcriptional regulation